ANALISIS KEBUTUHAN BAHAN AJAR LIVEWORKSHEETS DENGAN PEMBELAJARAN MATEMATIKA REALISTIK INDONESIA UNTUK MENINGKATKAN KETERAMPILAN LITERASI NUMERASI PELAJAR DILIHAT DARI RAPOR SEKOLAH - Lukman El Hakim; Darmastuti, Lintang (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
Teaching materials are the main component in supporting the learning process. Teaching materials that are adjusted to the characteristics of students' needs can improve students' mathematical skills, one of which is numeracy skills. These skills are very much needed by individuals in the 21st century. The purpose of this study was to determine the analysis of the needs of teaching materials needed by students so that they can improve their numeracy skills with realistic mathematics learning based on liveworksheets. This research method is quantitative descriptive with data collection using survey results distributed via google form. The survey was conducted on junior high school students in the Cijantung area. The results of the study indicate that the development of teaching materials is needed to improve numeracy skills in these schools with realistic mathematics learning based on liveworksheets.